Accuracy of Postpartum Hemorrhage Coding in the Swedish Pregnancy Register. Issue 4 (22nd December 2021) - Ladfors, L.V.; Muraca, G.M.; Butwick, A.; Edgren, G.; Stephansson, O.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100:322–330) Postpartum hemorrhage (PPH) is a major cause of maternal morbidity and mortality worldwide. Evaluating trends related to PPH depends on the accuracy of diagnostic codes, namely the International Classification of Diseases, 10th revision codes (ICD-10). The accuracy of these codes has not been widely reported and is relevant to research and quality improvement endeavors. The aim of this study was to assess the accuracy of ICD-10 codes for PPH in Sweden.